Evaluation of anthropometric parameters based on emotional eating - Martina Gažarová; Natalia Tobola (Roczniki Panstwowego Zakladu Higieny, 2025)
Background Emotions and moods are important regulators of food intake. While initially excessive intake, especially of unhealthy foods, was associated with negative emotions, now the emphasis is also on positive ones.